The effect of heavy reflector on neutronic parameters of core. (April 2022) - Košt'ál, Michal; Losa, Evžen; Czakoj, Tomáš; Schulc, Martin; Šimon, Jan; Juříček, Vlastimil; Rypar, Vojtěch; Ulmanová, Jana; Trkov, Andrej; Capote, Roberto
Highlights: Measurement of critical parameters of variously reflected core arrangements. Measurement of fission density across cores with various neutron reflectors. Calculation of criticality and spatial distribution of neutron flux in studied cores. Discrepancies between calculation and experiment. Abstract: The reactor baffle is an important component of a nuclear reactor that fixes the location of the fuel assembly in the reactor core. The main types of baffles are called light or heavy. The light baffle has mostly the form of steel plates with outer space filled by water, and the heavy baffle is mostly a forged steel element. Both concepts have advantages as well as disadvantages. In the case of the light baffle, one does not need to solve the issue of void swelling, but the neutron economy is not ideal, while the heavy baffle has a good neutron economy, but void swelling is an issue. This paper deals with the effect of the heavy VVER-1000 baffle on criticality. Criticality was measured using a well-defined core composed of 6 fuel assemblies moved to a simulator of the VVER-1000 internals, which is located at the LR-0 reactor. The experiments confirm the fact that the water filling the cooling channels in the baffle has a strong neutron-absorbing effect. The keff calculated using the ENDF/B-VIII.0 library significantly underpredicts the experiment. The calculations using a new evaluation of 56 Fe by the IAEA (INDEN collaboration) do not improve the situation significantly. Generally, the presented results are suitable for the validation of iron cross sections.